As Elders in Our Villages: Re-Imagining Racist and Anti-Indianist Public Schools. (3rd July 2021) - Haynes Writer, Jeanette; Baptiste, H. Prentice
Abstract : The authors, a Cherokee woman and an African American man, write from the important stance of multicultural education Elders, working from the foundational concept of the community as a village to raise a child. They discuss the caste system in the U.S. and briefly outline the historical and contemporary dehumanizing and assimilative actions of racism and anti-Indianism waged against communities, and specifically children in public schools. The authors then move to Elders? demands for the protection of children and call for public schools to institute practices such as funds of knowledge. They conclude with their personal and professional obligations and responsibilities to prepare teachers to be effective for all children, ensuring the well-being and cultural continuance for the children of their respective communities.